The Bacterial Composition within the Sarracenia purpurea Model System: Local Scale Differences and the Relationship with the Other Members of the Food Web - Gray, Sarah M.; Akob, Denise M.; Green, Stefan J.; Kostka, Joel E. (PLOS ONE, 2012)
The leaves of the carnivorous pitcher plant, Sarracenia purpurea, contain a microscopic aquatic food web that is considered a model system in ecological research. The species identity of the intermediate and top trophic level of this food web, as well the detritivore midge, are highly similar across the native geographic range of S. purpurea and, in some cases, appear to have co-evolved with the plant. However, until recently, the identity, geographic variation, and diversity of the bacteria in the bottom trophic level of this food web have remained largely unknown. This study investigated bacterial community composition inside the leaves of S. purpurea to address: 1) variation in bacterial communities at the beginning of succession at the local scale in different areas of the plant’s native geographic range (southern and mid-regional sites) and 2) the impacts of bacterial consumers and other members of the aquatic food web (i.e., insects) on bacterial community structure. Communities from six leaves (one leaf per plant) from New York and Florida study sites were analyzed using 16S ribosomal RNA gene cloning. Each pitcher within each site had a distinct community; however, there was more overlap in bacterial composition within each site than when communities were compared across sites. In contrast, the identity of protozoans and metazoans in this community were similar in species identity both within a site and between the two sites, but abundances differed. Our results indicate that, at least during the beginning of succession, there is no strong selection for bacterial taxa and that there is no core group of bacteria required by the plant to start the decomposition of trapped insects. Co-evolution between the plant and bacteria appears to not have occurred as it has for other members of this community.